Implementation of the Delphi technique in finance - Marcin Kozak; Olesia Iefremova (e-Finanse: Financial Internet Quarterly, 2014)
In the rapidly developing world, forecasting is very important for numerous aspects of our lives, the finance realm not being an exception. Various qualitative and quantitative methods are used to predict what is ahead. One of them is the Delphi method, an anonymous, structured discussion among experts on the forecasted topic. Developed over 60 years ago, it is one of the most effective qualitative forecasting and decision-making techniques. That said, literature review suggests Delphi's advantages have not been sufficiently utilized in financial research. This paper is an introduction to Delphi with a focus on the method's application possibilities in finance and related disciplines. For this purpose, we performed a literature review and presented a step-by-step guide for implementing the Delphi technique, describing a structure of the Delphi process, major principles of Delphi, experts' selection, Delphi types, ways of establishing consensus, validity of the method among others. Finally, we focused on implementing Delphi in finance and offered example topics that could be studied with Delphi.
Keywords: C53; E17; D84; F37; 330; Delphi method; financial forecasting; structured discussion